Poly(ɛ‐caprolactone)/gelatin composite electrospun scaffolds with porous crater‐like structures for tissue engineering. Issue 4 (1st February 2016) - Hwang, Patrick T.J.; Murdock, Kyle; Alexander, Grant C.; Salaam, Amanee D.; Ng, Joshua I.; Lim, Dong‐Jin; Dean, Derrick; Jun, Ho‐Wook
Abstract: Electrospinning has been widely used to fabricate scaffolds imitating the structure of natural extracellular matrix (ECM). However, conventional electrospinning produces tightly compacted nanofiber layers with only small superficial pores and a lack of bioactivity, which limit the usefulness of electrospinning in biomedical applications. Thus, a porous poly(ε‐caprolactone) (PCL)/gelatin composite electrospun scaffold with crater‐like structures was developed. Porous crater‐like structures were created on the scaffold by a gas foaming/salt leaching process; this unique fiber structure had more large pore areas and higher porosity than the conventional electrospun fiber network. Various ratios of PCL/gelatin (concentration ratios: 100/0, 75/25, and 50/50) composite electrospun scaffolds with and without crater‐like structures were characterized by their microstructures, surface chemistry, degradation, mechanical properties, and ability to facilitate cell growth and infiltration. The combination of PCL and gelatin endowed the scaffold with both structural stability of PCL and bioactivity of gelatin. All ratios of scaffolds with crater‐like structures showed fairly similar surface chemistry, degradation rates, and mechanical properties to equivalent scaffolds without crater‐like structures; however, craterized scaffolds displayed higher human mesenchymal stem cell (hMSC) proliferation and infiltration throughout the scaffolds after 7‐day culture. Therefore, these results demonstrated that PCL/gelatin composite electrospun scaffolds with crater‐like structures can provide a structurally and biochemically improved three‐dimensional ECM‐mimicking microenvironment. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1017–1029, 2016.